(untitled) (Dhaka University Law Journal, 2025)
The mediation process is widely regarded as an effective, flexible, and economical means of disposal of banking and financial disputes around the world because it provides unique opportunities for parties to consider all dimensions of the disputes, including legal, financial, and emotional aspects in a confidential environment. In the year of 2010, Bangladesh formally introduced the mediation process as a mandatory mechanism for the settlement of loan recovery disputes within the legal framework of “Artha Rin Adalat Ain” [hereinafter referred to as Money Loan Court Act, 2003(MLCA)]. However, over one decade of introduction, the mandatory mediation process has not yet reaped its potential as an alternative process to facilitate the disposal of banking and financial disputes. Consequently, the mediation process exhibits a notably low rate of case resolution when contrasted with the substantial number of pending loan recovery disputes in the court. This article seeks to explore the reasons behind the ineffective implementation of mediation in dealing with loan recovery disputes in Bangladesh. It aims to identify the procedural challenges that Money Loan Courts encounter when attempting to enforce existing laws relating to mediation and suggests potential reforms to enhance the efficacy and desirability of mediation in resolving money loan disputes. This article argues that significant challenges still prevail related to the effective application of the mandatory mediation process in resolving loan recovery disputes, which must be addressed by comprehensive legal and institutional reforms. It is projected that the innovative use of mandatory mediation will reduce the backlog of cases and facilitate the resolution of loan recovery disputes in an expeditious manner. Dhaka University Law Journal, 2025, 36 (1), 171-192